Nocturnal Cleaning Interactions Between the Giant Moray (Gymnothorax javanicus) and the Clear Cleaner Shrimp (Urocaridella antonbruunii) - Daniel M. Cryan; Kelsey M. Vaughn; Eleanor M. Caves (Ecology and Evolution)
ABSTRACT We observed a novel, nocturnal cleaning interaction between a cleaner shrimp (Genus Urocaridella) and the giant moray eel (Gymnothorax javanicus) on a lagoonal patch reef in Moorea, French Polynesia. Over the course of an 85‐min foraging bout (recorded on video by a snorkeler), we observed three separate, stereotyped cleaning interactions between G. javanicus and a cleaner shrimp in the genus Urocaridella (which surveys of Moorea biodiversity previously visually identified as Urocaridella antonbruunii). During these interactions, the shrimp would slowly crawl along one of the eel's flanks towards its head, enter its mouth, emerge on the other side of its head, then crawl back towards the reef along the eel's opposite flank, often causing it to jolt in response. On each of the visits, the moray spent roughly 9–12 min at the cleaning station and was observed being cleaned for a total of 62 s. Although this was a chance observation of only a few instances of cleaning, it may have several important implications for our understanding of the behavioral ecology of cleaning mutualisms, including (1) indicating potential temporal trade‐offs between being cleaned and foraging in eels, (2) suggesting a degree of temporal niche partitioning among sympatric cleaner species and (3) updating our understanding of cleaner‐client communication, given the nocturnal nature of our observations.